Manaadam, Eat Sparingly of it: A Wiindigoo on the French River in 1838 - Mazinegiizhigoo-kwe Bédard, Renée (Ontario History, 2025)
Stories of wiindigoo have been passed down for generations by the Anishinaabeg. This article reflects on an account of the “man eater” on the French River in the 1830s, and the extraordinary steps taken by community leaders to ensure the safety of its citizens. The article works to understand these horrific accounts and toward what Anishinaabeg legal scholar Kegedonce, or John Borrows, calls Bimeekamaugaewin, a binding set of principles to maintain harmony in both human and more-than-human communities.